Prevalence of adverse pathology features in grade group 2 prostatectomy specimens with syn‐ or metachronous metastatic disease. Issue 3 (8th December 2021) - Ma, Christopher; Downes, Michelle; Jain, Rahi; Ientilucci, Marc; Fleshner, Neil; Perlis, Nathan; van der Kwast, Theodorus
Abstract: Background: To validate the importance of recently established adverse histopathology features (cribriform pattern and intraductal carcinoma) as contra‐indication for deferred treatment of Gleason score 7 (3 + 4) (grade group [GG] 2) prostate cancer, we investigated their frequency in GG2 radical prostatectomies with syn‐ or metachronous metastatic disease. Methods: GG2 prostatectomy specimens of patients with concomitant lymph node metastasis or distant metastasis at follow‐up were identified in a clinical database of a tertiary care center and their pathology was reviewed for pathological stage, lymphovascular invasion, Gleason grade 4 subpatterns, presence of tertiary grade 5, and ductal adenocarcinoma histology. A control group of 99 GG2 prostatectomy specimens who had no metastatic disease (controls) was reviewed for the same adverse pathological features. Results: Of 1860 GG2 prostatectomy specimens (operated between 2002 and 2020), 45 (2.4%) had concurrent regional lymph node metastases or distant metastases at follow‐up. Pathological stage distribution of cases and controls was 24% and 79% pT2, 42% and 15% pT3a, 33% and 6.1% pT3b ‐T4, respectively ( p  < 0.001). Eleven of 45 cases (24%) had ≤10% Gleason grade 4 component. Cribriform pattern or intraductal carcinoma was present in 84% of cases versus 34% of controls ( p  < 0.001), tertiary grade 5 in 16% of cases versus 5% controls ( p  = 0.05) and ductal adenocarcinoma in 16% of cases versus 2% of controls ( p  = 0.004). Among the seven cases without cribriform or intraductal carcinoma, two displayed ductal adenocarcinoma features. Conclusions: Well‐established unfavorable histopathologic features (intraductal and cribriform pattern carcinoma, ductal adenocarcinoma) are represented in about 90% of GG2 prostate cancers with local or distant metastatic disease and are much less common (38%) in those without metastatic disease. Strikingly, about 25% of GG2 prostatectomy cases with metastatic disease had an organ‐confined disease and/or a small percentage of Gleason grade 4 pattern. This further emphasizes the relative importance of these adverse histopathological features (cribriform, intraductal, and ductal adenocarcinoma) rather than percentage Gleason grade 4 as contra‐indicator of deferred treatment for patients with GG2 prostate cancer.